An investigation into the socio-historical influences overcoming ethnicity in the early New Testament Church - Zgambo, Humphreys Frackson (Stellenbosch Theological Journal, 2017)
Ethnicity, tribalism and xenophobia could be found inside and outside church walls. Ethnicity and racism are natural, learned and nurtured in human beings. However, ethnic identity and relations exist whether the ethnic groups are competing or not. The first challenge of the early church in the New Testament Church was to overcome ethnicity and hostile divisions between Jews, Gentiles and Samaritans. This study aims at exploring how socio-historical influences and nature of the message of the New Testament managed to overcome ethnicity and ethnic divisions in the early New Testament Church. The study will also reflect on how the contemporary church could manage ethnicity within its structures and redefine its position on what it means to be one in Christ within the diverse church.